The manifestations of maintaining civilization through the story of DhulQarnayn in the chapter of the surah Al-Kahf - Mohamed Fathy, Mohamed Abdelgelil; Najmiah, Omar; Nur Sakiinah, Ab Aziz (2019)
There is no doubt that whoever seeks guidance by the Holy Qur’an will be guided, and whoever seeks heal for his body, spirit and life by it will be healed. This is considered one of the axioms for those who have adopted the Holy Qur’an a source of guidance. However, some people may believe that as the Holy Quran came down on the Arabs in the past, it is good for their condition and not good for the progress, development and civilization in the era of technology and satellite channels. This constitutes the problem of research. Thus, the research aims at demonstrating the extent of the Qur’an’s talk about civilization and clarifying its invitation to preserve the civilization. It highlights the models and stories that have refinely been cultivated and civilized, and the reasons which whoever adheres to them has maintained that civilization. This article is carried on based on the analytical approach, so it presents the story of Dhul-Qarnayn from which the bases of civilization will be extracted and the means by which the preservation of that civilization will maintained. From that we conclude that the Holy Quran calls to civilization, development and progress contrary to what some think. In addition, the Holy Quran proves that for everything there is a cause. Whoever aspires to have a civilization he should exert his efforts to obtain those means. Moreover, this article found that the Holy Quran left nothing but talk about it. The Holy Qur’an has not talked about the civilization of Dhul-Qarnayn, but mentioned the means of the modernity, development and civilization and the bases of maintaining that civilization.